Oral Astaxanthin Supplementation Prevents Peritoneal Fibrosis in Rats. Issue 5 (September 2015) - Wakabayashi, Keiichi; Hamada, Chieko; Kanda, Reo; Nakano, Takanori; Io, Hiroaki; Horikoshi, Satoshi; Tomino, Yasuhiko
Background: Preventing peritoneal damage during peritoneal dialysis is critical. Reactive oxygen species (ROS) have an important role in peritoneal damage; however, few studies have investigated this. We aimed to determine the effects of oral astaxanthin (AST) supplementation in a peritoneal fibrosis (PF) rat model. Methods: Thirty-seven Sprague-Dawley rats were divided into 5 groups: Control 1 (fed a normal diet without stimulation), Control 2 (fed an AST-supplemented diet without stimulation), Group 1 (fed a normal diet with 8% chlorhexidine gluconate [CG] stimulation for 3 weeks), Group 2 (fed a 0.06% AST-supplemented diet with CG stimulation), and Group 3 (fed a 0.06% AST-supplemented diet that was initiated 4 weeks before CG stimulation). Peritoneal fibrosis, vascular proliferation, and fibrosis-related factor expression were examined. Results: Peritoneal thickness was significantly suppressed by AST supplementation. Astaxanthin diminished the number of CD68-, 8-hydroxy-2'–deoxyguanosine (8-OHdG)-, and monocyte chemoattractant protein-1 (MCP-1)-positive cells. Type 3 collagen, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and MCP-1 mRNA expression was significantly lower in Group 3 than in Group 1. Increased transforming growth factor-β (TGF-β) and Snail mRNA expression, vascular density, and the number of α–smooth muscle actin (α–SMA)-positive cells were also decreased in Group 3. Conclusion: Astaxanthin suppressed PF development through the inhibition of inflammation and oxidation in PF rats. It appears that the anti-oxidative agent AST may be useful for the prevention of peritoneal damage.